Factor out the common term 4
-4(2x - y) = 24
Divide both sides by -4
2x-y= - 24/4
Simplify24/4 to 6
2x -y = -6
Subtract 2x from both sides
-y = -6 - 2x
Multiply both sides by -1
y = 6 + 2x
Step-by-step explanation:
f(x) = (3/2)ˣ
g(x) = (2/3)ˣ
These are examples of exponential equations:
y = a bˣ
If b > 1, the equation is exponential growth.
If 0 < b < 1, the equation is exponential decay.
So f(x) is an example of exponential growth, and g(x) is an example of exponential decay.
Also, 2/3 is the inverse of 3/2, so:
g(x) = (3/2)^(-x)
So more specifically, f(x) and g(x) are reflections of each other across the y-axis.
Answer:
6.39*10^-4
Step-by-step explanation:
according to the form that is used to convert usual into scientific notation it be like 6.39*10^-4
12.28 = 12 and 28 hundredths so its 12
![\frac{28}{100}](https://tex.z-dn.net/?f=%20%5Cfrac%7B28%7D%7B100%7D%20)
Hope I helped!